The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ejvssr.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial Vertebral Artery Aneurysm Rupture Complicated by Extrapleural Haematoma

Abstract: IntroductionExtracranial vertebral artery aneurysm (EVAA) and extrapleural haematoma (EH) are rare clinical findings most often associated with blunt or penetrating trauma. However, EVAA rupture can be complicated by development of a large EH.ReportA 50 year old man underwent an emergency thrombectomy followed by graft reconstruction of an aorto-bi-femoral bypass. The post-operative course was complicated by respiratory failure and severe anaemia. Computed tomography revealed EVAA rupture and EH, so ligation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…As for direct surgery, trapping and ligation were performed under thoracotomy. 3 , 34) When the aneurysm is located in the thoracic cavity, direct surgery is invasive and the complication rate is comparatively high due to surgical insults to the thoracic cavity, including excision of the clavicle, ribs, and sternum. 35) Morimoto et al reported that extracranial VAns were treated by direct surgery in combination with bypass and that one patient developed a cerebral infarction due to delayed occlusion of a saphenous vein graft two months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As for direct surgery, trapping and ligation were performed under thoracotomy. 3 , 34) When the aneurysm is located in the thoracic cavity, direct surgery is invasive and the complication rate is comparatively high due to surgical insults to the thoracic cavity, including excision of the clavicle, ribs, and sternum. 35) Morimoto et al reported that extracranial VAns were treated by direct surgery in combination with bypass and that one patient developed a cerebral infarction due to delayed occlusion of a saphenous vein graft two months after surgery.…”
Section: Discussionmentioning
confidence: 99%